Estimation of soil erosion by the “Rusle” model of the zhylandy river basin (Journal of Geography and Environmental Management, 2021)
Soil erosion is a serious problem resulting from agricultural intensification, land degradation and other anthropogenic activities.Soil erosion assessment is useful when planning and conducting conservation work on a watershed or basin. Modeling can provide a quantitative and consistent approach to estimating soil erosion and sediment release over a wide range of conditions. In this study, the universal soil loss equation (RUSLE) integrated with GIS was used to estimate soil loss in the Zhylanda basin located in the Northern part of Kazakhstan. Parameters of the RUSLE model were estimated using remote sensing Data, and zones of probability of erosion were determined using GIS. Estimated indicators of soil erodibility range from 0.001 to 1.631 t / year. The results obtained indicate that the estimated total annual potential soil loss is about 189.17 t / year. The predicted rate of soil erosion due to the increase in the area of agricultural land is about 250 t / year.As a result of the study, a map of the probability zone of erosion was obtained using the weighted overlay index method, which shows that a significant part of the studied area falls into the zone of high and very high probability of an erosion process.
Keywords: soil, erosion, river basin, modeling, GIS.